A Hairy Situation: Laser Hair Removal after Oral Reconstruction. (March 2018) - Shields, Bridget E.; Moye, Molly S.; Bayon, Rodrigo; Sperry, Steven M.; Wanat, Karolyn A.
Objectives: To present a case series of 4 patients who underwent postoperative hair removal using the long-pulsed Alexandrite or Nd:YAG laser following intraoral cutaneous flap reconstruction. Methods: Patients underwent epilation in dermatology clinic with long-pulsed Alexandrite or Nd:YAG lasers, spaced 8 weeks apart, until hair removal was achieved. Results: All patients achieved improvement in hair removal regardless of initial flap donor site with significant improvement in quality of life and minimal side effects. Conclusions: The long-pulsed Alexandrite and Nd:YAG represent safe and effective treatment options to improve patient quality of life following intraoral flap repair following excision of malignancy.